CORRELATION OF WAVEGUIDES WITH ELECTRICALLY CONDUCTIVE LAYERS IN CONTINENTAL CRUST - Rezanov I.A.; Derlyatko Y.K.; Krasnopevtseva G.V. (My University, 1988)
The paper first discusses the two independent methods of directly determining the changes in a physical variable with depth in the interior of the earth, namely seismic and electromagnetic sounding. It then considers the geological interpretation of waveguides and conductive layers, using as examples two of the most thoroughly studied structural types: cratonic shields, and continental rifts. Subjects covered include reasons that waveguides and conductive layers occur at the same, relative shallow, depths in rift zones, but not on shields, and others.